Control over the Morphology and Plasmonic Properties of Rod-like Au-Pd Bimetallic Nanostructures. Issue 3 (April 2021) - Deng, Tian-Song; Zhang, Qi; Wei, Ming-Zhang; Gu, Yi-Jie; Cheng, Zhiqun
Abstract: Bimetallic nanostructures are interesting materials for many applications ranging from plasmonics to catalysis. However, synthesizing bimetallic nanorods with good control over composition, morphology and maintaining an anisotropic shape is challenging. Here, we have shown a reproducible approach to the synthesize the bimetallic core-shell nanorods within a stabilizing mesoporous silica shell and with an Au core and a Pd metal shell with excellent control over their properties. Specifically, we demonstrate that the thickness and morphology of the Pd metal shell (rough/smooth) can be precisely tuned and studied the plasmonic properties of the resulting bimetallic nanostructures in detail. Our approach can be naturally extended to different or more than two metals leading to rod-shaped metal particles with highly tunable materials properties that are of interest in their use in optical and catalytic applications.